Hydro-cooling as means to retain fresh sweet corn ears quality - Ding, Phebe; Raja Mat, Raja Norhidayu (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sweet corn ear is a highly perishable produce with short postharvest life due to its high respiration rate which depletes sugar concentration in kernel. As a result, ear loses its sweetness and quality within 1 to 2 days under room temperature. Hydro-cooling after harvest is a good practice as it can reduce the metabolism and respiration rate of the produce. Thus, the objective of this study was to determine the effectiveness of hydro-cooling in retaining quality of sweet corn ears. Freshly harvested sweet corn ears were immersed in hydro-cooler to achieve its half and seven-eighth cooling time. Pre-cooled and non-pre-cooled ears were then stored at 12±2 and 25±2 °C for 8 days and quality index, weight loss, pH, soluble solids concentration, titratable acidity and ascorbic acid of ears were evaluated at 2 days interval. The experiment was arranged in randomized complete block design with factorial arrangement (three cooling times  two storage temperatures  five storage days) and then repeated thrice. Differences between cooling time  storage temperature, cooling time  storage day, storage temperature x storage day and cooling time  storage temperature  storage day were significant on quality index of ears. Storage temperature  storage day was also significant on ears weight loss, soluble solids concentration and pH. Seven-eight cooling time and storage at 12±2 °C provide the best quality index of ears; retain higher soluble solids concentration and pH with significantly lower weight loss compared to other cooling time treatment and 25±2 °C storage temperature. In short, temperature management is crucial in manipulating sweet corn ears quality.